Financial shock transmission to heterogeneous firms: The earnings-based borrowing constraint channel - Livia Chiţu; Magdalena Grothe; Tatjana Schulze; Ine Van Robays (European Central Bank (ECB), 2023)
We study the heterogeneous impact of jointly identified monetary policy and global risk shocks on corporate funding costs. We disentangle these two shocks in a structural Bayesian Vector Autoregression framework and investigate their respective effects on funding costs of heterogeneous firms using micro-data for the US. We tease out mechanisms underlying the effects by contrasting financial frictions arising from traditional asset-based collateral constraints with the recent earnings-based borrowing constraint hypothesis, differentiating firms across leverage and earnings. Our empirical evidence strongly supports the earnings-based borrowing constraint hypothesis. We find that global risk shocks have stronger and more heterogeneous effects on corporate funding costs which depend on firms' position within the earnings distribution.
Keywords: G12; E43; E52; 330; corporate spreads; earnings-based borrowing constraint; heterogeneous firms; monetary policy shocks; global risk shocks